NUMERICAL SOLUTION OF EULER EQUATION BASED ON FINITE VOLUME METHOD WITH UPWIND FLUX SCHEME FOR TRANSONIC AIRFOIL - Iqbal Faisal, Muhammad
Stegger and Warming Flux Vector Splitting scheme has been developed to solve the Euler equations system based on finite volume method. The schemes were used to solving the high speed problems. Algebraic grid by using Transfinite interpolation has been used to generated the initial grid. The elliptic grid used to improve the quality of grid. Alternative discretizations methods can be developed which relate to the physical propagation properties of the solutions of the Euler equations. These ‘non?space?centred’ schemes are classified as upwind schemes in a global sense, since many variants can be defined. Their common point is the relation established between the characteristic propagation properties and the differencing such as to apply directional space discretizations in accordance with the physical behaviour of the inviscid flows. Stegger and Warming Flux Vector Splitting scheme is one of the upwind schemes. This scheme has been employed at this work. The case study in this research are airfoil NACA 0012 and airfoil RAE 2822. The results of simulation which is the flow properties were compared with other data available in literature. Validation has been done to prove reliability this code.